The Product Chains of Rare Earth Elements Used in Permanent Magnets and NiMH Batteries for Electric Vehicles - Eriksson, Therese; Olsson, David (My University, 2011)
This master thesis will address the topic of rare earth metals and their product chain from early mining processes, through refining to final products and recycling. The analysis will cover the global product chain and its different actors. Rare earth metals consist of 17 elements of the periodic table; the 15 lanthanides, scandium and yttrium. Despite their name, these elements are not rare, but quite abundant all over the earth’s crust. Nevertheless, their concentration in the deposits is often very low and they are difficult to extract and refine. The rare earth metals are similar in their characteristics and can be used for many different applications. Rare earths are commonly used in green technology since their unique properties can save weight and increase efficiency in products such as light bulbs, generators in wind power plants, and in different parts of hybrid and electric vehicles. The focus in this report will be on the product chains of the rare earth metals used in permanent magnets and batteries used in hybrid and electric vehicles, these are: neodymium, praseodymium, lanthanum, dysprosium, cerium and terbium. In nature these elements do not occur as metals and many complicated processes are needed to convert them into metals. The product chain starts with the mining and separation processes, next comes further refining and separation processes, and then production of rare earth metals and alloys before they can be shaped into parts in a final product. In total China has more than 95% of the global market for mining and separation processes for rare earth metals, also the production of rare earth metals and alloys occur to a large extent in China. The production of most permanent magnets also takes place in China, but there is also production in Japan, Finland and Germany. Japanese car manufacturers have most of their parts produced within Japanese borders, which means that most permanent magnets used in hybrid and electric vehicles are produced in Japan. The same is true for the NiHM batteries, about 95 % of those that are inside these vehicles today are produced in Japan by Japanese manufacturers. The markets for green technology seem to expand, creating an increasing demand for rare earth metals. To meet the demand with a larger supply there is need for solutions such as new mining projects, reopening of closed mines, or recycling and recovering of rare earths from scrap products and mine tailings. The urge for more supply of rare earth metals and also rising prices presents a good incentive for recycling and recovering different rare earth metals from discarded products. These recycling and recovering processes are technically and often economically very demanding. Today there are processes that could recover rare earths with a high level of purity, but the problem is often the huge costs for the processes as well as handling of waste chemicals and materials that might be toxic. New processes will have to be developed. There has been research for new processes, and recycling/recovering plants are planned to be constructed in Japan as well as other countries. This report will also look at the potential for having parts of the rare earth product chain in Sweden, since the country has both the physical resources and also metallurgical knowledge. With this in mind we discussed the possibilities of eventually operating the processes in the product chain in Sweden, and aspects of this scenario.
Keywords: Miljöteknik; Environmental engineering